Inosine triphosphatase deficiency helps predict anaemia, anaemia management and response in chronic hepatitis C therapy. Issue 12 (24th June 2013) - Clark, P. J.; Aghemo, A.; Degasperi, E.; Galmozzi, E.; Urban, T. J.; Vock, D. M.; Patel, K.; Thompson, A. J.; Rumi, M. G.; D'Ambrosio, R.; Muir, A. J.; Colombo, M.
Summary: Anaemia frequently complicates peginterferon/ribavirin therapy for chronic hepatitis C infection. Better prediction of anaemia, ribavirin dose reduction or erythropoietin (EPO) need, may enhance patient management. Inosine triphosphatase (ITPA) genetic variants are associated with ribavirin‐induced anaemia and dose reduction; however, their impact in real‐life clinic patient cohorts remains to be defined. We studied 193 clinic patients with chronic hepatitis C infection of mixed viral genotype (genotype 1/4 n = 123, genotype 2/3, n = 70) treated with peginterferon/ribavirin. Patients were genotyped for ITPA polymorphisms rs1127354 and rs7270101 using Taqman primers. Hardy–Weinberg equilibrium was present. Estimated ITPA deficiency was graded on severity (0–3, no deficiency/mild/moderate/severe, n = 126/40/24/3, respectively). Multivariable models tested the association with anaemia at 4 weeks of treatment [including decline in haemoglobin (g/dL); haemoglobin <10 g/dL and haemoglobin decline >3 g/dL]; ribavirin dose reduction and EPO use and explored sustained viral response (SVR) to peginterferon/ribavirin. More severe ITPA deficiency was associated with less reduction in haemoglobin level ( P < 0.001; R 2 = 0.34), less ribavirin dose reduction (OR 0.42; (95% CI = 0.23–0.77); P = 0.005) and less EPO use [OR 0.53; (0.30–0.94); P = 0.029]. ITPA deficiency was associated with SVR [OR: 1.70; (1.02–2.83); P = 0.041] independently of clinical covariates (adjusted R 2 = 0.31). In this clinical cohort, ITPA deficiency helped predict the risk of on‐treatment anaemia, ribavirin dose reduction, need for EPO support and was associated with SVR. For patients on HCV regimens including peginterferon/ribavirin, testing for ITPA deficiency may have clinical utility.